2013
DOI: 10.15580/gjbs.2013.5.061313672
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability, Heritability and Genetic Advance in Cowpea Genotypes in Two Agro-ecological Environments

Abstract: Studies on genetic variability, heritability and genetic advance were carried out with five genotypes of cowpea (Vigna unguiculata L. Walp) cultivated at two (rainforest and guinea savannah) agroecological environments. Analysis of variance revealed that though there was no significant interaction among the genotypes for most of the characters studied, they varied significantly for all the 16 characters at each of the two locations, indicating the existence of considerable variation for all the characters. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 16 publications
17
19
0
Order By: Relevance
“…This development is not unexpected considering the dynamic nature of climatic variables and its complex interplay with biological properties of plant. This result corroborates Nwosu et al (2013) that reported about 54 days to flowering and 70 days pod maturity in 6 cowpea varieties evaluated in Ibadan (tropical-transition rain forest) and Keffi (guinea savannah). The preponderance of individuals with early-medium maturity and absence of individuals with very prolonged (delay) flowering and indeterminate fruiting characteristics deed indicate that these cowpea varieties are products of advance breeding program for earliness and determinate flowering and fruiting characteristics.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This development is not unexpected considering the dynamic nature of climatic variables and its complex interplay with biological properties of plant. This result corroborates Nwosu et al (2013) that reported about 54 days to flowering and 70 days pod maturity in 6 cowpea varieties evaluated in Ibadan (tropical-transition rain forest) and Keffi (guinea savannah). The preponderance of individuals with early-medium maturity and absence of individuals with very prolonged (delay) flowering and indeterminate fruiting characteristics deed indicate that these cowpea varieties are products of advance breeding program for earliness and determinate flowering and fruiting characteristics.…”
Section: Discussionsupporting
confidence: 92%
“…Data on wide genetic variability in cowpea for morphological (phenotypic) attributes are well documented (Apte et al 1987;Damarany 1994;Idahosa et al 2010;Manggoel et al 2012;Nwosu et al 2013). The results obtained here is in slight contrast to study by Nwosu et al (2013) that showed non-significant effect of location for all yield components Phenotypic Analysis of Yield Components in Cowpea • 257 including flowering and maturity periods in six varieties of cowpea evaluated in Keffi (guinea savannah ecology) and Ibadan (tropical rainforest ecology). This kind of variation between studies could be attributed to sample size, genotype, and factors of location instead of years as in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This observed variation might be due to environmental factors rather than genetic ones. Similar results have been reported by Nwosu et al (2013). The heritability in broad sense was significantly higher for all the traits under investigation, it ranged from (86.2 to 99.9%).…”
Section: Correlation Coefficientssupporting
confidence: 88%
“…The expression of wide genetic variability recorded in this study offers opportunity for quality improvement that would allow selection of individuals with better attributes for maturity period and grain yield. Reports on wide genetic variability in cowpea phenotypic attributes are available (Manggoel et al, 2012;Nwosu et al, 2013). The range of values recorded for flowering and pod maturity, suggest that the varieties were predominantly early to medium maturing; and the range values for the grain yield indicated that the selected cowpeas comprised low to very high yielding varieties.…”
Section: Pc1 -6096%mentioning
confidence: 99%